2019
DOI: 10.1111/jace.16788
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis and annealing of tungsten di‐ and tetra‐boride

Abstract: Tungsten diboride and tetra‐boride were synthesized by a combination of mechanochemical method and the subsequent heat treatment. To clarify the formation process of tungsten diboride (WB2) and tetra‐boride (WB4) using W‐B mixture system with variable B concentration, the effects of ball‐to‐powder ratio, W to B molar ratio on mechanochemical process were studied, and the relationship between phase composition and annealing temperature was built. The results show that, the synthesis of WB2 with W:B = 1:5 can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…[1][2][3][4] A number of transition metal borides have Vicker's hardness greater than 40 GPa and bulk modulus larger than 300 GPa, which, coupled with their metallic nature and inexpensiveness, makes them excellent materials for superhard coating and cutting tools. [5][6][7][8] A vast number of superhard metal borides with various crystal structures has been discovered in recent years, including mono- 8,9 , di- 5,6,10 , tetra- [11][12][13][14] , and dodecaborides 15,16 , as well as their solid solutions. It has been experimentally shown that the hardness of materials of this class can be controlled through intrinsic-originating from local chemical bonding-and extrinsic-resulting from surface grain boundaries and pattering-hardening effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] A number of transition metal borides have Vicker's hardness greater than 40 GPa and bulk modulus larger than 300 GPa, which, coupled with their metallic nature and inexpensiveness, makes them excellent materials for superhard coating and cutting tools. [5][6][7][8] A vast number of superhard metal borides with various crystal structures has been discovered in recent years, including mono- 8,9 , di- 5,6,10 , tetra- [11][12][13][14] , and dodecaborides 15,16 , as well as their solid solutions. It has been experimentally shown that the hardness of materials of this class can be controlled through intrinsic-originating from local chemical bonding-and extrinsic-resulting from surface grain boundaries and pattering-hardening effects.…”
Section: Introductionmentioning
confidence: 99%
“…A vast number of superhard metal borides with various crystal structures have been discovered in recent years, including mono-, , di-, ,, tetra-, and dodecaborides, , as well as their solid solutions. It has been experimentally shown that the hardness of materials of this class can be controlled through intrinsic originating from local chemical bondingand extrinsic resulting from surface grain boundaries and patterninghardening effects.…”
Section: Introductionmentioning
confidence: 99%
“…The catalysts synthesized by molten salt differ from carbothermal reduction ones in terms of peak intensity and broadening, implying that the XRD peaks of W (1‐ x ) TM x B 2 /ms catalysts are broader in contrast to those of W (1‐ x ) TM x B 2 /ct. As a result, W (1‐ x ) TM x B 2 /ms samples are more nano‐sized compared to the W (1‐ x ) TM x B 2 /ct ones 33 . Scherrer’s equation is applied to calculate the average particle size (D) of the nanoparticles for each sample (peak 101). D=kλ/βcosθ. where k = 0.94 is the shape factor of a particle, presuming the shape of the nanoparticles as a sphere, λ = 1.5406 Å is the wavelength of Cu Kα radiation, β is the FWHM of the XRD (101) peak, and θ is the diffraction angle of the peak 29 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, W (1-x) TM x B 2 /ms samples are more nano-sized compared to the W (1-x) TM x B 2 /ct ones. 33 Scherrer's equation is applied to calculate the average particle size (D) of the nanoparticles for each sample (peak 101).…”
Section: Characterizationmentioning
confidence: 99%
“…[1][2][3][4] A number of transition metal borides have Vicker's hardness greater than 40 GPa and bulk modulus larger than 300 GPa, which, coupled with their metallic nature and inexpensiveness, makes them excellent materials for superhard coating and cutting tools. [5][6][7][8] A vast number of superhard metal borides with various crystal structures has been discovered in recent years, including mono- 8,9 , di- 5,6,10 , tetra- [11][12][13][14] , and dodecaborides 15,16 , as well as their solid solutions. It has been experimentally shown that the hardness of materials of this class can be controlled through intrinsic-originating from local chemical bonding-and extrinsic-resulting from surface grain boundaries and pattering-hardening effects.…”
Section: Introductionmentioning
confidence: 99%